STUDY THE EFFECTIVENESS APPLICATIONS OF FUZZY CONTROLLER WITH TWO ENTRANCES IN THE SYSTEM OF ACTIVE QUEUE MANAGEMENT THE PACKETS IN TCP/IP NETWORKS - O. V. Nevdachyna; A. P. Polonevych; A. S. Artyuschyk (Системный анализ и прикладная информатика, 2016)
The paper presents an approach to solving the overloading problem in TCP/IP networks. Offered fuzzy controller with two inputs for system of active queue management packages in TCP/IP networks, and investigated its use in these systems with a random change of traffic load. Proposed controller has two inputs, one of which is the value of the difference between the current queue length and the second – the difference between the current level of usage of the buffer. The output of the fuzzy controller calculates the probability of discarding packet.Mathematical model system of active queue management that is studied is presented in an interactive MATLAB system, in wherein also is demonstrated the processes occurring in the system with a random change of traffic load. The research results show that the AQM-system with fuzzy controller with two entrances stable enough maintains the desired current length the queue for sufficiently small values of the probability of dropping/marking packets (at acceptable size of queue q0= 200 packets, the average probability of dropping / marking is not more than 3,5×10–3 or less 0,35% packets is discarded or marked from the total number of incoming packets). The results obtained will help improve the efficiency of the functioning and operation of TCP / IP networks by increasing data transmission quality. this happens due introduction of the proposed controller at the design of new, more efficient routers for networks to minimize the delay of information.